EMI based monitoring of early-age characteristics of concrete and comparison of serial/parallel multi-sensing technique. (10th December 2018) - Bharathi Priya, C.; Jothi Saravanan, T.; Balamonica, K.; Gopalakrishnan, N.; Rao, A. Rama Mohan
Highlights: Monitoring of early age strength in concrete due to improper curing using PZT. Experimental investigations on cube and beam using smart sensing PZT units (SSU). Multisensing serial/parallel technique of sensors for faster interrogation. Significance of using plates of differing thickness in SSUs while multi-sensing. Theoretical background to separate electrical & mechanical coupling in MISO mode. Invariant factor between the ratio of parallel and series admittance. Abstract: Changes in admittance signatures measured using Electro-Mechanical Impedance (EMI) technique with a lead zirconate titanate (PZT) transducer, embedded in concrete is an indirect estimate of the localised changes in dynamic stiffness of the concrete in the proximity of the sensor. Experiments and observations of the EMI signatures obtained from PZT sensors bonded onto identical plates and embedded in concrete cubes with two sets of curing have been presented. Also, experiments are conducted on a concrete beam embedded with six PZT sensors bonded on carrier plates of differing thickness by subjecting the beam to differential curing. Feature extraction on the admittance signatures is carried out to identify the early age strength gain characteristics in the concrete. EMI measurements have been continued for 28 days until the signatures asymptote to vanishing changes. The contribution of the present work is the application of serial/parallel connected sensors embedded in concrete (in a Multi Input Single Output, MISO mode), that can be typically deployed in a large scale structural health monitoring (SHM) scenario. A novel methodology for separating the electrical and mechanical coupling in a multiplexed sensing scenario is a notable contribution. A hitherto unreported invariant factor which is obtained as the ratio of the parallel and serial admittance signatures is reasoned out and the removal of this results in separating the constant electrical admittance from the mechanical admittance. Well separated resonant peaks in the admittance signature is a pre-requisite for tracking and observing the changes, which is achieved through plates of different thickness resulting in different ultrasonic resonant modes. In the composite EMI signature which is representative of many sensors, individual peaks could be associated with separate sensors and their influencing regions.